2017
DOI: 10.20886/jphka.2017.14.2.99-100
|View full text |Cite
|
Sign up to set email alerts
|

MODEL KEBERHASILAN DAN MANAJEMEN PENANGKARAN CUCAK RAWA (Pycnonotus zeylanicus)

Abstract: Straw-headed bulbul (Pycnonotus zeylanicus) is a popular singing bird widely traded in Indonesia. Captive breeding is one of the conservation efforts to increase the population outside the natural habitat, therefore, research on captive breeding models is important. The objective of the study is mainly to describe the management and determine the model of straw-headed bulbul captive breeding. The study was conducted on May-July 2015 in 10 different captive breeding facilities in Bogor and Depok Districts. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The assessment of trade in strawheaded bulbuls is a follow-up study of Bergin et al [ 46 ], who reported on the trade in this species in 12 wildlife markets in 8 cities on Java and Kalimantan over a one-year period (July 2014 to June 2015), during which 71 birds in total were observed. Strawheaded bulbuls are listed as Critically Endangered on the IUCN Red List and are protected in Indonesia, but commercial breeders do breed the species [ 47 ]. Captive-bred strawheaded bulbuls often, but not always, have closed legrings, so their presence is strong evidence of the birds having been captive-bred.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of trade in strawheaded bulbuls is a follow-up study of Bergin et al [ 46 ], who reported on the trade in this species in 12 wildlife markets in 8 cities on Java and Kalimantan over a one-year period (July 2014 to June 2015), during which 71 birds in total were observed. Strawheaded bulbuls are listed as Critically Endangered on the IUCN Red List and are protected in Indonesia, but commercial breeders do breed the species [ 47 ]. Captive-bred strawheaded bulbuls often, but not always, have closed legrings, so their presence is strong evidence of the birds having been captive-bred.…”
Section: Methodsmentioning
confidence: 99%